2008
DOI: 10.1590/s0100-204x2008001200005
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of stored-product insects to phosphine

Abstract: -The objectives of this work were to assess phosphine resistance in insect populations (Tribolium castaneum, Rhyzopertha dominica, Sitophilus zeamais and Oryzaephilus surinamensis) from different regions of Brazil and to verify if the prevailing mechanism of phosphine resistance in these populations involves reduced respiration rates. Sixteen populations of T. castaneum, 15 of R. dominica, 27 of S. zeamais and eight of O. surinamensis were collected from 36 locations over seven Brazilian states. Each populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 21 publications
0
42
0
8
Order By: Relevance
“…Here, three populations of the lesser grain borer Rhyzopertha dominica (Coleoptera: Bostrichidae), one of the main worldwide pests of stored cereals, were exposed to sublethal concentrations of phosphine, and their walking behaviour was recorded. These populations differ in their life history traits, particularly in developmental and population growth rates, which had been recognised earlier and associated with phosphine resistance and its associated physiological cost 25, 28, 29. The present hypothesis was that exposure to phosphine would lead to a reduction in walking activity as a protective behaviour.…”
Section: Introductionmentioning
confidence: 81%
“…Here, three populations of the lesser grain borer Rhyzopertha dominica (Coleoptera: Bostrichidae), one of the main worldwide pests of stored cereals, were exposed to sublethal concentrations of phosphine, and their walking behaviour was recorded. These populations differ in their life history traits, particularly in developmental and population growth rates, which had been recognised earlier and associated with phosphine resistance and its associated physiological cost 25, 28, 29. The present hypothesis was that exposure to phosphine would lead to a reduction in walking activity as a protective behaviour.…”
Section: Introductionmentioning
confidence: 81%
“…This insect is mainly controlled using synthetic insecticides (organophosphates or pyrethroids) and fumigation, phosphine being remarkable as the main fumigant used (LORINI;GALLEY, 1999;GONÇALVES et al, 2007). However, studies revealed phosphine resistance in Brazilian R. dominica populations (ATHIÉ et al, 2001;PIMENTEL et al, 2008), which could render the use of these products unviable if alternative methods are not implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Price (1984) suggested that the mechanism is the reduced uptake of phosphine and it is likely to be accepted because respiration is a good factor observing a physiological response of an insect to the environmental changes (Chaudhry et al, 2004). Pimentel et al (2008) also reported that phosphine resistance in four coleopteran insect pests (T. castaneum, R. dominica, S. zeamais, and O. surinamensis) collected from 36 locations over seven Brazilian states is related to the reduced production of carbon dioxide. Comparing with the respiration rates between the most resistant and the most susceptible populations to the fumigant, the carbon dioxide production of the former is significantly (P < 0.05) lower than that of the latter.…”
Section: Resistance To Insecticidesmentioning
confidence: 99%